Pengaruh Harga Pada Kualitas Terhadap Penjualan Kemiri Menurut Hukum Islam: (Studi Kasus Pasar XII Kelurahan Binjai Serbangan Kecamatan Air Jomankabupaten Asahan) - Nasution, Syahrul; Nurwandri, Andri; Atikah, Dewi (Islamic Education Journal, 2023)
Price is the value of a good or service which is measured by the amount of money spent by the buyer to obtain a combination of goods or services and their services. The problem formulation in this research is: How to know the quality of candlenut products in Pasar XII, Binjai Serbagan District, Kec. Joman Water. What is the quality and price of candlenut products at Pasar XII, Binjai Serbagan District, Kec. Air Joman. and how does price influence product quality from an Islamic perspective on candlenut sales at Pasar XII, Binjai Serbagan District, Kec. Joman Water. The research method for this type of thesis research is field research and field observation to obtain the desired data. Apart from that, it is also based on library research, using qualitative research methods, where the stages of data collection, data processing and data analysis are carried out simultaneously and interactively. From the results of the author's research it can be seen that: From the results of the hypothesis test (t test) regarding price versus quality regarding the price of candlenut products at Pasar XII, Binjai Serbagan District, Kec. Air Joman, it was stated that there was a significant positive influence of price on candlenut purchasing decisions (t count of 2.746 > t table of 1.68385). while the coefficient of determination value which is the result of R square is 0.159 namely 15.9% and the remaining 84.1% which is influenced by other variables not examined in this research.